2021
DOI: 10.1007/s10557-021-07189-9
|View full text |Cite
|
Sign up to set email alerts
|

The Redox Modulating Sonlicromanol Active Metabolite KH176m and the Antioxidant MPG Protect Against Short-Duration Cardiac Ischemia-Reperfusion Injury

Abstract: Purpose Sonlicromanol is a phase IIB clinical stage compound developed for treatment of mitochondrial diseases. Its active component, KH176m, functions as an antioxidant, directly scavenging reactive oxygen species (ROS), and redox activator, boosting the peroxiredoxin-thioredoxin system. Here, we examined KH176m’s potential to protect against acute cardiac ischemia-reperfusion injury (IRI), compare it with the classic antioxidant N-(2-mercaptopropionyl)-glycine (MPG), and determine whether prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…We have recently reported paradoxical improvement and detrimental signaling, angiogenesis, and endothelial function with short-term versus long-term endothelium-specific NOX2 OE, respectively, in a transgenic animal model, highlighting the importance of EC mito-ROS homeostasis [ 49 , 50 ]. Since the finding that a short-term increase in NOX2-derived ROS results in the upregulation of MnSOD and angiogenesis, several studies have reported beneficial effects of MnSOD-mimetics on cardiac recovery and angiogenesis [ 15 , 19 , 66 ]. However, the mito-ROS scavenging agents used in those studies were not EC-specific and thus might have modulated mito-ROS of different cell types including cardiomyocytes, vascular smooth muscle cells, and fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently reported paradoxical improvement and detrimental signaling, angiogenesis, and endothelial function with short-term versus long-term endothelium-specific NOX2 OE, respectively, in a transgenic animal model, highlighting the importance of EC mito-ROS homeostasis [ 49 , 50 ]. Since the finding that a short-term increase in NOX2-derived ROS results in the upregulation of MnSOD and angiogenesis, several studies have reported beneficial effects of MnSOD-mimetics on cardiac recovery and angiogenesis [ 15 , 19 , 66 ]. However, the mito-ROS scavenging agents used in those studies were not EC-specific and thus might have modulated mito-ROS of different cell types including cardiomyocytes, vascular smooth muscle cells, and fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…14 In line with our current results, the active metabolite of this drug has reduced IR-induced cardiac damages and corrected mitochondrial myopathy by modifying mitochondrial redox activity. 10 The protective effects of this drug have been dependent on the duration of ischemia. Previous studies have shown that this drug modifies the biological consequences of mitochondrial complex-1 dysfunction (seen in Leigh syndrome).…”
Section: Discussionmentioning
confidence: 99%
“…In the KH-receiving groups, the KH176 was intraperitoneally injected into rats at concentrations of 10 μM (KH10) and 50 μM (KH50), 10 min before establishing reperfusion. 10 The drug was prepared in 1% DMSO and the non-treated IR animals received the same volume of DMSO intraperitoneally. To inhibit mK-ATP channels, 5-Hydroxydecanoate (5HD) at a concentration of 5 μM was injected intraperitoneally 5 min before injection of KH176 at 50 μM.…”
Section: Sample Size Calculation and Animal Groupingmentioning
confidence: 99%
See 1 more Smart Citation
“…Sonlicromanol (KH176, Figure 4) is an antioxidant agent targeting the thioredoxin redox systems [48]. Recently, it obtained an orphan drug designation for maternally inherited diabetes and deafness [49] and it is now in phase IIB clinical trials for mitochondrial disease treatments [50]. Sonlicromanol is a chiral drug [51] that, after metabolization, retains the same stereochemistry and it has been suggested to be a substrate for CYP3A4 [52,53].…”
Section: Sonlicromanolmentioning
confidence: 99%